Dood & Verderf? De bijdrage van geestelijke verzorging aan de beeldvorming over religie - Körver, Sjaak (Religie & Samenleving, 2017)
The imagery of religion in the media is usually negatively coloured and stereotyped, emphasizing the conflicting and violent sides and highlighting the differences. This imagery is in sharp contrast with the experiences of chaplains working in prison, the army, youth care, and care institutions. Although their position is often unclear and under pressure, they are actually asked for assistance in case of existentially serious events. Usually clients and caregivers (especially nurses) know when to appeal to them. Opposite the negative framing of religion in the media chaplains create positive images of religion dealing with the boundaries of existence in a personal way. Stories about these experiences can counterbalance the unilaterally hostile image of religion. Rituals, an attitude of hospitality and common humanity, and especially the awareness that we share in the same fragility of life appear to play an essential role.